Storage Limitation Statements: Temperature – Fungicides - Frederick M. Fishel (EDIS)
This 7-page fact sheet provides information about how temperature affects storage of agricultural fungicides. A table is included that lists many common agricultural fungicides registered for use in Florida along with storage limitations. It was written by Frederick M. Fishel, and published by the UF Department of Agronomy, March 2013.